Situational Testing Tasks as a Means of Diagnosis of Subject Competences of the Future Teachers of Technologies of Specialized School (by the Example of the Subject «Fundamentals of Sewing Production») - Khrenova, Viktoriya (Pedagogical Discourse, 2013)
The article deals with the creation of situational tests as a means of diagnosing the level of formation of subject competencies students-future teachers technology that will teach high school students the basics of sewing business. It analyses the essence of the concepts of «test», «testing». Based on the analysis of scientific publications in the studied subjects found type tests that can be used as a tool for diagnosing competencies of future teachers technology specialized schools. Competence-oriented situational test tasks (by the example of the subject «Fundamentals of Sewing Production») are developed and presented.